2014
DOI: 10.3163/1536-5050.102.3.007
|View full text |Cite
|
Sign up to set email alerts
|

Searching ClinicalTrials.gov and the International Clinical Trials Registry Platform to inform systematic reviews: what are the optimal search approaches?

Abstract: For systematic reviews, trials registers and major bibliographic databases should be searched. Trials registers should be searched using sensitive approaches, and both the registers consulted in this study should be searched.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 27 publications
(58 reference statements)
1
77
0
Order By: Relevance
“…Eysenbach et al [20] provide an approach to internet searching for unpublished clinical trials. There are published studies on searching specific resources systematically, for example, Google Scholar [2124] and trials registers [25]. Outside of the systematic review literature, Blakeman [26] outlines challenges and approaches for searching Google effectively and discusses other online resources and tools for retrieving research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eysenbach et al [20] provide an approach to internet searching for unpublished clinical trials. There are published studies on searching specific resources systematically, for example, Google Scholar [2124] and trials registers [25]. Outside of the systematic review literature, Blakeman [26] outlines challenges and approaches for searching Google effectively and discusses other online resources and tools for retrieving research.…”
Section: Introductionmentioning
confidence: 99%
“…Glanville et al [25] studied search approaches for two clinical trials registries, ICTRP and Clinicaltrials.gov, and found single-concept searches in the basic interfaces to be the most reliable. Haddaway et al [24] investigated approaches for searching Google Scholar, which only displays the first 1000 references of a search; they found that title searches enabled discovery of more grey literature (conference proceedings, theses, reports) than full-text searches.…”
Section: Introductionmentioning
confidence: 99%
“…Trial registration numbers (TRNs) may assist identification of a protocol for a known trial but do nothing to assist retrieval of previously unknown trials that match the inclusion criteria for a systematic review. The plethora of terms and synonyms required to achieve sensitive retrieval of such trials from a trial register may prove prohibitive given registers' limited functionality when compared with bibliographic databases . Empirical studies are required to establish (i) what proportion of trial protocols are retrievable by using pragmatic methods of retrieval, (ii) what the most effective methods for retrieving protocols are, (iii) what the main barriers in retrieving protocols are, and (iv) whether the most easily retrieved copy of the protocol remains the document of record.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of which concept to use in each register is likely to differ. Glanville recommends, for example, that when searching the ICTRP, searches using more than 1 concept should be constructed with caution because the Boolean operators are processed in a specific order within the interface and nesting is not supported. Effective searches of the ICTRP require repetitive use of terms, for example repeating the disease with each intervention as shown in the following example of nails for tibial fractures:
tibia* AND nail* OR tibia* AND pin* OR tibia* AND screw* OR tibia* AND plate* OR tibia* AND fix* OR tibia* AND prosthe* OR tibia* AND ream* OR tibia* AND unream*
…”
Section: Searching Trials Registers and Other Resourcesmentioning
confidence: 99%